Facebook Intervention to Connect Alaska Native People With Resources and Support to Quit Smoking: CAN Quit Pilot Randomized Controlled Trial. Issue 4 (20th September 2022) - Patten, Christi A; Koller, Kathryn R; Sinicrope, Pamela S; Prochaska, Judith J; Young, Colleen; Resnicow, Kenneth; Decker, Paul A; Hughes, Christine A; Merritt, Zoe T; McConnell, Clara R; Huang, Ming; Thomas, Timothy K
Abstract: Introduction: There is some evidence that social media interventions can promote smoking cessation. This randomized controlled pilot study is the first to evaluate the feasibility and potential efficacy of a Facebook smoking cessation intervention among Alaska Native (AN) adults. Aims and Methods: Recruitment and data collection occurred from December 2019 to March 2021. Participants were recruited statewide in Alaska using Facebook advertisements with a targeted sample of 60 enrolled. Participants were stratified by gender, age, and rural or urban residence and randomly assigned to receive referral resources on evidence-based cessation treatments (EBCTs) (control, n = 30) or these resources plus a 3-month, closed (private), culturally tailored, Facebook group (intervention, n = 31) that connected participants to EBCT resources and was moderated by two Alaska Native Trained Tobacco Specialists. Assessments were conducted online post-randomization at 1, 3, and 6 months. Outcomes were feasibility (recruitment, retention, and intervention engagement), self-reported use of EBCTs, and biochemically confirmed seven-day point-prevalence smoking abstinence. Results: Of intervention participants, 90% engaged (eg posted, commented) more than once. Study retention was 57% at 6 months (no group differences). The proportion utilizing EBCTs was about double for intervention compared with the control group participants at 3 and 6 months. Smoking abstinence was higher for intervention than control participants at 3 months (6.5% vs. 0%, p = .16) but comparable at 6 months (6.4% vs. 6.7%, p = .97). Conclusions: While additional research is needed to promote long-term cessation, this pilot trial supports recruitment feasibility during the Coronavirus Disease 2019 (COVID-19) pandemic, consumer uptake, and a signal for intervention efficacy on the uptake of cessation treatment and short-term smoking abstinence. Implications: This study is the first evaluation of a social media intervention for smoking cessation among Indigenous people. We learned that statewide Facebook recruitment of AN adults who smoke was feasible and there was a signal for the efficacy of a Facebook intervention on the uptake of EBCT and short-term (3 months) biochemically verified smoking abstinence. Clinically, social media platforms may complement current care models by connecting AN individuals and others living in hard-to-reach communities to cessation treatment resources.